2018
DOI: 10.3389/fmicb.2018.00278
|View full text |Cite
|
Sign up to set email alerts
|

How to Control HTLV-1-Associated Diseases: Preventing de Novo Cellular Infection Using Antiviral Therapy

Abstract: Five to ten million individuals are infected by Human T-cell Leukemia Virus type 1 (HTLV-1). HTLV-1 is transmitted through prolonged breast-feeding, by sexual contacts and by transmission of infected T lymphocytes through blood transfusion. One to ten percent of infected carriers will develop a severe HTLV-1-associated disease: Adult-T-cell leukemia/lymphoma (ATLL), or a neurological disorder named Tropical Spastic Paraparesis/HTLV-1 Associated Myelopathy (TSP/HAM). In vivo, HTLV-1 is mostly detected in CD4+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 92 publications
0
33
0
Order By: Relevance
“…However, the effect is only transient in HAM/TSP patients [ 40 ], and may be related to temporal fluctuations in viral RNA and response to immune control mechanisms in these patients [ 250 , 251 , 252 ]. Improved therapies include VPA combinations with zidovudine (AZT) or cytokines (IFNα) [ 253 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect is only transient in HAM/TSP patients [ 40 ], and may be related to temporal fluctuations in viral RNA and response to immune control mechanisms in these patients [ 250 , 251 , 252 ]. Improved therapies include VPA combinations with zidovudine (AZT) or cytokines (IFNα) [ 253 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, attention has been recently paid to a novel generation of NRTIs anti-HIV drugs, i.e., the acyclic nucleoside phosphonates (ANP). In particular, prodrugs of the already mentioned TFV, also named as PMPA [9-R-(2-phosphonomethoxypropyl)adenine], were investigated in a new model of HTLV-1 infection in vitro using as recipient cells LTR luciferase reporter Jurkat T-cells [25]. Interestingly the results showed that the RT inhibitors, acyclic nucleotide analogue of adenosine adefovir (or PMEA), and its pro drug, adefovir dipivoxil (or bis-POM-PMEA) were found to be more active than AZT in inhibiting HTLV-1 infection in vitro while the pro-drugs of PMPA, such as tenofovir disoproxil (bis-POC-PMPA), TDF and TAF (tenofovir alafenamide) had more effect than TFV.…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Adult T-cell leukemia (ATL) patients are mainly treated with drugs that target infected cells regardless of their ability to express the virus (Miyazato et al, 2016), while HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) are treated with drugs reducing inflammation but not the proviral load (Futsch et al, 2017). Nevertheless, reducing the proviral load remains a promising strategy and screening of antivirals that target viral replication and viral dissemination are ongoing (Macchi et al, 2011;Pasquier et al, 2018;Barski et al, 2019).…”
Section: Escape From Therapeutics Strategiesmentioning
confidence: 99%